Progressive intrahepatic cholestasis (Byler's disease): case report. Issue 12 (December 1975) - De Vos, R; de Wolf-Peeters, C; Desmet, V; Eggermont, E; Van Acker, K
Abstract : This paper reports the case of a child in which the clinical and laboratory data indicate a progressive intrahepatic cholestasis of the type described as Byler's disease. The histological and histochemical findings suggest an intrahepatic cholestasis. Electron microscopy reveals interruptions of the bile canalicular membrane, which have been described as characteristic of this disease. A striking feature in the present case is the remarkable increase of microfilamentous structures in the pericanalicular ectoplasm and in the hepatocytic cytoplasm. The findings suggest a primary disturbance in bile acid secretion as the casue of cholestasis, entailing a hypertrophy of pericanalicular microfilaments which supposedly play a role in the final step of biliary secretion.